(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The need for food continues to increase along with the increase in world population. However, problems in environmental, social and economic aspects arise because some of the food will end up being wasted, in fact, this food waste is produced at every stage in the food supply chain. This problem needs to be of concern to both the government as a regulator and business actors as operators and the public as consumers. Based on research conducted by the Ministry of National Development Planning, the proportion of food waste is mostly generated at the consumption stage. The consumption stage is divided by two actors, food service and households. This paper focuses on discussing the generation of food waste in food services in Jakarta using a causal loop analysis. This study aims to propose a strategy for managing food waste in the food service sector. Causal loop analysis provides an understanding of the flow of food waste generation and the relationship between variables that affect food waste generation. The causal loop diagram provides an overview of the generation of food waste generated from three sources: food suppliers, food services and food banks. Three scenarios are implemented to reduce the level of food waste generation.